The Validity of IPAS Module based on STEM to Improve Students' Scientific Literacy Skills - Umi Hanik; Erman Erman; Pirim Setiarso (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2023)
Objective: This study describes the validity of based inquiry change textbooks used to train students' scientific literacy skills. The validity of the developed inquiry-based textbooks is viewed from the aspects of content feasibility, presentation feasibility, linguistic feasibility, inquiry suitability, and scientific literacy. Method: This study used the development of the 4D model (define, design, and develop), which was modified and implemented in the Science Education Postgraduate Program at Surabaya State University. The data collection technique was carried out using the textbook validation method. The assessment instrument used was a textbook validation sheet that two chemistry lecturers validated as validators. Data analysis was carried out quantitatively and descriptively. Results: The research results are in the form of validation of STEM-based textbooks, with an average score of 91.20% in the very valid category. Novelty: The novelty of this research is that there are STEM-based features in textbooks about change that can improve students' scientific literacy skills. Based on the data analysis, the developed inquiry-based textbooks are valid and suitable for learning.